Pengaruh Komunikasi Mengajar Guru Pendidikan Agama Kristen Terhadap Minat Belajar Siswa Kelas X TKR SMK Negeri 2 Siatas Barita Tapanuli Utara Tahun 2023/2024 - Liha Sari Nadeak; Dorlan Naibaho; Frainskoy Rio Naibaho; Lince R.T Simamora; Roida Lumbanttobing (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The aim of this research is to determine the influence of Christian Religious Education Teachers' Teaching Communication on Learning Interest of Class X TKR Students at SMK Negeri 2 Siatas Barita North Tapanuli in 2023/2024. The research method used is a descriptive quantitative method. The population was all 101 students of class X TKR SMK Negeri 2 Siatas Barita who were Christians and a sample of 50 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 35 items, namely 16 items for variable Siatas Barita North Tapanuli 2023/2024, proven through the following data analysis: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.469 > rtable(a=0.05,n=50) = 0.297. b) Testing a significant relationship obtained tcount= 3.680 > ttable(a=0.05, dk=n-2=48)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂="29.49"+0.64X. b) Regression coefficient of determination test (r2) = 22%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=20, dk denominator=n-2=50-2=48) namely 13.53 > 1.51. Thus Ha is accepted and H0 is rejected.